PENGGUNAAN VARIASI TRAY PADA PENGOLAHAN AIR SUMUR BOR - Budi Nining Widarti (INFO-TEKNIK, 2016)
Drilled water well or groundwater is one of clean water sources which often contains high concentration of iron (Fe) and manganese (Mn) with low concentration of pH. The concentration of Fe, Mn and pH in the water that does not comply with quality standards may adversely affect the health of humans. The purpose of this study was to determine the optimum removal efficiency value for Fe, Mn and optimum value of difference in increasing for pH from the point of multiple tray aerator inlet-sedimentation outlet, overall treatment, and determine the quality of water sample at the end of outlet for each parameter in all variations of tray. On this research the variations were performed on multiple tray aerator was the first, second, third, fourth, fifth tray variation including the number of tray storey at 1, 2, 4, 6 and 8 tray.Based on the research that had been done at the point of multiple tray aerator inlet-sedimentation outlet, the optimum removal efficiency value for Fe occurred at the second tray variation of 61,93 %, Mn at the fourth tray variation of 35,69 %. The optimum value of difference in increasing for pH occurred at the fifth tray variation of 1,6. At the point of overall treatment, the optimum removal efficiency value for Fe occurred at the fourth tray variation of 100,00 %, Mn at the second tray variation of 99,68 %. The optimum value of difference in increasing for pH occurred at the fifth tray variation of 2,6.